A STATISTICAL STUDY OF TRAFFIC ACCIDENTS IN THE CITY OF LONDRINA-PR IN 2019 - CARDOSO, Meiri das Graças; MARTINS, Rogerio Mendonça; STURION, Leonardo (Brazilian Journal of Biometrics, 2021)
This article addressed traffic accidents in the urban perimeter of the city of Londrina- Paraná, Brazil, carried out in 2019. The information used was from the Integrated Emergency Trauma Care System and collected through the General Occurrence Registry (RGO) of the Fire Department of Londrina. For this study, accidents were selected in the collision category between vehicle drivers and motorized drivers. The study variables were the most frequent months and the accident codes defined by Integrated Trauma Emergency Service (SIATE). The article aimed to analyze the occurrences (collision) of vehicle drivers in 2019, seeking to make the population aware of accident prevention. The methodology adopted was descriptive, quantitative, obtained intentionally. The results show that these categories of drivers are responsible for more than 50% of the total accidents and more than 60% of the fatal victims. According to the results obtained, it is expected that the authorities may be sensitized, adopting measures that lead those responsible to more rigorous sanctions, thus making drivers aware of having greater responsibility when driving a vehicle, emphasizing that they need to redouble their attention and have responsibility in traffic, avoiding negligence and damage to the lives of others.